2010 IEEE Second International Conference on Social Computing 2010
DOI: 10.1109/socialcom.2010.40
|View full text |Cite
|
Sign up to set email alerts
|

Churn in Social Networks: A Discussion Boards Case Study

Abstract: Churn has been identified as an important issue in a wide range of industries. In social networks, churn represents a significant risk for the health and functioning of communities. However, the importance and actual meaning of churn in social networks is almost unexplored. This work provides a general view on these issues and discusses aspects that are especially relevant to discussion boards. We provide a broad literature review on "traditional" churn analysis and prediction and highlight the specialities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 17 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Most relevant to our work is the hazard-based modeling of Kapoor et al [19] on LASTFM. Other related work includes user engagement patterns in social networks [20,35].…”
Section: Related Workmentioning
confidence: 99%
“…Most relevant to our work is the hazard-based modeling of Kapoor et al [19] on LASTFM. Other related work includes user engagement patterns in social networks [20,35].…”
Section: Related Workmentioning
confidence: 99%
“…Much research has been carried out on analyzing social media channels with different perspectives in mind; privacy issues [10], [11], influential users within a community [12], [13], [14], churns in online social communities [15], trending topic classifications [16], [17] etc. In the last few years, research has also started to emerge on analyzing the activities of software developers with respect to software projects on social media channels.…”
Section: Related Workmentioning
confidence: 99%
“…It is also worth noting that our proposed churn definition is simpler and more robust than the definition in [5], which is based on two time windows: a previous activity window and a churn window. That is, a user is labeled as churner if her activity in the churn window drops to some extent relative to the activity in the previous window.…”
Section: B Problem Formulationmentioning
confidence: 99%
“…Studies have shown that churn can be attributed to intrinsic and extrinsic factors [5], [6]; the former pertain to the customer profiles and/or inherent features of the service (such as customer's membership age, pricing, service failure rate, etc. ), while the latter portray the service in terms of the value it accrues through its social roles (e.g., community opinion, word-of-mouth effects, etc).…”
Section: Introductionmentioning
confidence: 99%